Ultraearly Hematoma Growth in Acute Spontaneous Intracerebral Hemorrhage Predicts Early and Long-Term Poor Clinical Outcomes: A Prospective, Observational Cohort Study - Wang, Wen-Juan; Lu, Jing-Jing; Liu, Li-Ping; Jia, Jiao-Kun; Zhao, Xing-Quan (Frontiers in Neurology, 2021)
Aims: Although prognostic importance of ultraearly hematoma growth (uHG) in acute, non-traumatic intracerebral hemorrhage (ICH) has been established for early outcomes, longer-term clinical outcomes are lacking. We aimed to determine the association of uHG with early and 1-year clinical outcomes after acute ICH in a larger and broader range of patients. Methods: We studied 589 patients with acute (<6 h) spontaneous ICH. uHG was defined as baseline ICH volume/onset-to-imaging time (OIT) (ml/h). Multivariable logistic regression analyses were performed to determine the association of uHG with in-hospital mortality, 90-day, and 1-year poor outcome [3 ≤ modified Rankin Scale (mRS)] after ICH. Results: The median speed of uHG was 4.8 ml/h. uHG > 9.3 ml/h was independently related to in-hospital mortality [odds ratio (OR) 2.81, 95% CI 1.52–5.23], 90-day poor outcome (OR 3.34, 95% CI 1.87–5.95), and 1-year poor outcome (OR 3.59, 95% CI 2.01–6.40) after ICH. The sensitivity of uHG > 9.3 ml/h in the prediction of in-hospital mortality, 90-day poor outcome, and 1-year poor outcome was 68.8, 48.0, and 51.1%, respectively. Conclusions: Ultraearly hematoma growth was a useful predictor of in-hospital mortality, 90-day, and 1-year poor outcome after acute ICH. The combination of both uHG and baseline ICH volume could allow better selection of patients with ICH at high risk of poorest clinical outcomes for future clinical trials to improve early- and long-term clinical outcomes.